Identifying the Relationship Between Crime and Unemployment in United States for the Period 1985-2022 - Sambou, Horoja (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
This research paper explored the connection between unemployment and property crime in United States utilizing annual time series data ranging from 1985 to 2022.The other explanatory variables such as poverty rate, real minimum wage was used along with unemployment to analyze their impact on property crime rates. The study adapted the autoregressive distributed lag cointegration (ARDL) method to test the hypothesis of long-term relationship between unemployment and property crime. The results obtained from this study were also supported by the economic theory of crime which revealed that an increase in unemployment rate will increase the rate of property crime. The ARDL method used revealed that there exists a long run relationship between property crime and unemployment. The study also employed different unit root test approaches such as ADF (Augmented Dickey-Fuller), PP (Phillips-Perron) and KPSS (Kwiatkowski-Phillips-Schmidt-Shin) to check for robustness in the results. The results obtained from the unit roots test showed that the variables are stationary at different order of integration I (0) and I (1). The model of this study was also free from autocorrelation and heteroskedasticity problems. The error correction model (ECM) demonstrated the speed of adjustment of the model when it is disequilibrium in the short run to the long run equilibrium. The ECM result showed that there is a speed of adjustment of about 60%.

ÖZ: Bu çalışma, 1985-2022 yılları arası verileri kullanarak Amerika Birleşik Devletlerinde işsizlik ile mülke karşı işlenen suçlar arasındaki ilişkiyi analiz etmektedir. İşsizlikle birlikte yoksulluk oranı ve reel asgari ücret seviyesi de mülke karşı işlenen suçlar da açıklayıcı değişken olarak kullanılmıştır. Çalışmada işsizlik ve suç arasında uzun dönemli ilişki bulunduğu hipotezini test etmek için otoregresif dağıtılmış gecikme eşbütünleşme (ARDL) yöntemi kullanıldı. Çalışmada elde edilen sonuçlar, iktisadi teoride açıklandığı şekilde işsizlik oranının arttıkça mülke karşı işlenen suçların da arttığı tezini doğrulamaktadır. ARDL yöntemine göre işsizlik ile mülke karşı işlenen suçlar arasında uzun dönemli bulunduğu görülmüştür. Ayrıca çalışmada, elde edilen parametre tahminlerinin sağlamlığını test etmek amacıyla ADF (Augmented DickeyFuller), PP (Phillips-Perron) ve KPSS (Kwiatkowski-Phillips-Schmidt-Shin) gibi farklı birim kök testleri kullanılmıştır. Farklı birim kök testlerinden elde edilen sonuçlar göstermiştir ki, modelde kullanılan değişkenler I(0) ve I(1) farklı entegrasyon derecelerinde de durağandırlar. Çalışmada kullanılan model otokorelasyondan ve değişen varyans sorunundan arındırılmıştır. Hata düzeltme modeli (ECM) de kullanılan modelin kısa vadedeki dengesizlik halinden uzun dönemde dengeye uyumlaşma hızını da göstermiştir. Hata düzeltme modeli uyumlaşma hızı %60 olarak hesaplanmıştır.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2024. Supervisor: Asst. Prof. Dr. Yenal Süreç.
Keywords: Economics Department; Unemployment--United States; Economic Conditions and Development--United States; Property Crime, Unemployment, ARDL Model, Time Series Data